The Role of Television Talk Shows on Iraqi Satellite Channels in Spreading Family Awareness Regarding Issues of Domestic Violence, An Analytical Study of a Program with Rafif Al-Hafiz, For the Period from (12/1/2023 to 2/1/2024) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research deals with a new problem in Iraqi society, which is (domestic violence), which has crossed all borders in society. Therefore, there has become an urgent need to study this phenomenon and determine its causes and the factors that control it. Therefore, the researcher divided this study.The research was divided into three chapters (the first chapter) was entitled the methodological framework and the importance and problem of the research and previous studies were explained, and the second chapter was the theoretical framework: in which social networking sites and domestic violence were explained, while the third chapter was a content analysis of the study.